Antenatal calcium intake in Malaysia - Rahmah, Mohd Amin; Zaleha, Abdullah Mahdy; Hashimah, Basri (2014)
Aim: To determine the adequacy of antenatal calcium intake in Malaysia, and the influencing factors. Methods: A cross-sectional study was conducted among postnatal women who delivered in two tertiary hospitals. Data were collected from antenatal cards, hospital documents and diet recall on daily milk and calcium intake during pregnancy. SPSS version 19.0 was used for statistical analyses. Results: A total of 150 women were studied. The total daily calcium intake was 834 ± 43 mg (mean ± standard error of the mean), but the calcium intake distribution curve was skewed to the right with a median intake of 725 mg daily. When calcium intake from milk and calcium supplements was excluded, the daily dietary calcium intake was only 478 ± 25 mg. Even with inclusion of milk and calcium supplements, more than a third (n = 55 or 36.7%) of the women consumed less than 600 mg calcium in their daily diet. The adequacy of daily calcium intake was not influenced by maternal age, ethnicity, income or maternal job or educational status as well as parity. Conclusion: The daily dietary calcium intake of the Malaysian antenatal population is far from adequate without the addition of calcium supplements and milk.